2019
DOI: 10.1210/clinem/dgz291
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism, Sex, and Age Predict Future Thromboembolic Events Among Younger People

Abstract: Purpose Aberrant thyroid function causes dysregulated metabolic homeostasis. Literature has demonstrated hypercoagulability in hypothyroidism, suggesting a risk for thromboembolic events (TEE). We hypothesize that individuals with hypothyroidism will experience more clinically-diagnosed TEE than euthyroid individuals. Methods De-identified patient data from the University of New Mexico Health Sciences Center were retrieved us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Subclinical hypothyroidism (SCH) is an endocrine and metabolic disorder that is characterized by elevated serum thyroid-stimulating hormone (TSH) above the upper limit of reference with normal serum free thyroid hormones (FT4 and FT3) ( 1 ). Recently, several studies have shown that SCH is associated with hypercoagulability ( 2 ), cardiovascular disease ( 3 ), dyslipidaemia ( 4 ), and increased carotid artery atherosclerosis ( 5 ). Atherosclerosis is a chronic inflammatory response with a complex pathological mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical hypothyroidism (SCH) is an endocrine and metabolic disorder that is characterized by elevated serum thyroid-stimulating hormone (TSH) above the upper limit of reference with normal serum free thyroid hormones (FT4 and FT3) ( 1 ). Recently, several studies have shown that SCH is associated with hypercoagulability ( 2 ), cardiovascular disease ( 3 ), dyslipidaemia ( 4 ), and increased carotid artery atherosclerosis ( 5 ). Atherosclerosis is a chronic inflammatory response with a complex pathological mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, female patients are at higher risk of autoimmune diseases, [30] and there is also a higher risk of having thyroid dysfunction along with other autoimmune diseases. [31] In addition, young and middle-aged women often have an increased risk of VTE due to oral contraceptives or bed rest during pregnancy and lower limb blood stasis. [32] Therefore, we found that women with thyroid dysfunction had a higher risk of VTE than men in the included studies, [19] and further large-scale cohort studies are still needed to evaluate further the association between gender and the risk of VTE after thyroid dysfunction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in antithrombin increases in homocysteine and factor VIII, and cardiovascular risk factors (arterial hypertension, hyperlipidemia, diabetes, and smoking) have previously been reported to be associated with SSNHL [ 30 ]. Hypercoagulability and increased risk of thromboembolism have been reported in hypothyroidism [ 31 ]. Thus, SSNHL patients may be at an increased risk of developing vascular insufficiencies driven by their thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%